Are men getting more emotional? Critical sociological perspectives on men, masculinities and emotions - de Boise, Sam; Hearn, Jeff (The Sociological Review, 2017)
Sociological research, influenced by feminist and other critical perspectives, has noted how men’s emotional inexpressiveness was influenced, and supported, by patriarchal privilege. Such approaches have argued that ‘inexpression’ needs to be broken down in order to build gender equality and improve men’s own wellbeing. Emerging research has, however, challenged the argument that men are ‘emotionally inexpressive’ on two main premises: that, as a result of feminist critiques, many men now practise ‘softer’ or ‘more emotional’ forms of masculinity; second, that emotions always influence social action and so need to be better incorporated into sociological accounts of men’s behaviour. Yet these approaches entail some conceptual confusion as to what emotions are, how they link to social action and whether men’s emotions are inherently transformative for gender relations. This article first details how emotions and masculinity have been theorized in feminist-inspired approaches. It outlines recent work on emotions, men and masculinities before arguing for an understanding of emotions that engages with both physiologically grounded and postconstructionist debates. It finally suggests incorporating a material-discursive approach to men’s emotions, through feminist work on affect, which is attentive to the political dimensions of ‘increasing emotionality’ in order to contribute to a developing field of sociological research.
https://www.researchgate.net/publication/313022582_Are_men_getting_more_emotional_Critical_sociological_perspectives_on_men_masculinities_and_emotions
Keywords: approches et analyses; discipline; genre; inégalités; masculinité; privilèges; rapports sociaux de sexe; ressource en ligne; sciences humaines; sociologie; systèmes d'oppressions; émotions

Co-construction of a data collection tool: A case study with Atikamekw women - Basile, Suzy; Hugo Asselin; Thibault Martin (ACME: An International Journal for Critical Geographies, 2017)
Dans les cultures Autochtones, les savoirs, les rôles et les pratiques étaient historiquement basés sur la réciprocité et la complémentarité entre les genres. En excluant les femmes Autochtones des processus de prise de décision, les politiques coloniales ont réduit la base de savoirs sur laquelle les décisions s'appuient. Les voix des femmes Autochtones ont longtemps été exclues des recherches et les chercheurs ont joué un rôle important dans leur marginalisation. C'est dans ce contexte – et dans un effort de décolonisation de la recherche – que nous présentons une étude de cas du processus de co-construction d'un outil de collecte de données avec des femmes Atikamekw. En préparant un projet de recherche sur le rôle des femmes Autochtones dans la gouvernance du territoire et des ressources naturelles, nous avons travaillé avec trois femmes Atikamekw, qui ont attribué une grande importance au processus d'obtention du consentement des participantes. Nous avons élaboré le formulaire de consentement ensemble, afin qu'il réponde à leurs préoccupations quant à la confiance, la transparence et l'implication de la communauté tout au long de la recherche. Décoloniser la recherche implique que les outils de collecte de données ne devraient pas être élaborés dans des bureaux universitaires, mais par une collaboration significative avec les participants à la recherche.
https://www.acme-journal.org/index.php/acme/article/view/1414
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; femmes Atikamekw; projet charge mentale; périodes historiques; racisme; recherche participative; régions géographiques; sexisme; système colonial; systèmes d'oppressions

CPS Women's research and action forum - O'Keefe, Jennifer (2017)
« The Changing Public Services (CPS) project’s Atlantic Cluster, based primarily in Halifax, Nova Scotia, concluded its research in the fall of 2016. To summarize their findings and to report back to the community, the cluster hosted a public event called the “Women’s Research and Action Forum”. The event brought together feminist academics, advocates, members of labour unions, students and others to not only learn about research results but to engage with it in an interesting and meaningful way. This paper summarizes and reflects on the events of the Forum » [Résumé original]
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; canada; forum; groupes de femmes; nouvelle-écosse; orpcc; outils; pour des recherches en milieux de pratiques; périodes historiques; recherche en milieux de pratique; ressource en ligne; régions géographiques

Writing intimacy into feminist geography - Moss, Pamela; Donovan, Courtney (Taylor & Francis, 2017)
Intimacy, expressed through the feelings and sensations of the researcher, is bound up in the work of a feminist geographer. Tapping into this intimacy and including it in academic writing facilitates a grasping of the effects of power in particular places and initiates a discussion about how to access and tease out what constitutes the intimate both ethically and politically throughout the research process. This collection provides valuable reflections about intimacy in the research process - from encounters in the field, through data analysis, to the various pieces of written work. A global and heterogeneous pool of scholars and researchers introduce personal ways of writing intimacy into feminist geography. ​ As authors expand existing conceptualizations of intimacy and include their own stories, chapters explore the methodological challenges of using intimacy in research as an approach, a topic and a site of interaction. The book is valuable reading for students and researchers of Geography, as well as anyone interested in the ethics and practicalities of feminist, critical and emotional research methodologies.
Keywords: LGBTQIA2+; approches et analyses; autobiographie; discipline; ethnographie; géographie; identités LGBTQIA2+; intimité; méthodologie; queer; sciences humaines; sociologie; thématiques; émotions; éthique

Feeling our way: Academia, emotions and a politics of care - Askins, Kye; Blazek, Matej (Social & Cultural Geography, 2017)
Cet article a pour but de mieux comprendre le rôle des émotions dans le monde universitaire, et leur implication dans le fait de produire et de défier une université normalisée de plus en plus néolibérale. Il découle de deux discours qui mettent les émotions au premier plan dans et à travers les espaces et les pratiques universitaires, afin d’explorer de façon critique comment les connaissances et les positions sont construites et comment on les fait circuler. Il continue ensuite par prendre en compte ces questions sous l’angle de la sensibilité en tant que position politique pour être et devenir un universitaire en ces temps néolibéraux. Notre but est de contribuer à la recherche qui se développe dans le domaine des géographies émotionnelles, en amenant ce travail de manière explicite dans la conversation des débats renaissants au sujet d’une éthique de sensibilité, comme faisant partie d’une politique qui critique l’individualisme et le gestionnariat dans le monde universitaire (et au-delà). Nous examinons les façons dont les structures universitaires néolibérales font circuler certains affects particuliers, qui induisent des émotions telles que le désir et l’anxiété ainsi que l’internalisation de la compétition et de l’évaluation en tant qu’universitaires incarnés. Nos récits donnent en exemple comment les émotions et les affects qui y sont liés peuvent faire écho et se reproduire de plus en plus à travers les cultures de l’université et se propager dans les vies personnelles et professionnelles. Nous soutenons que les émotions à l’université sont importantes, coproduisant mutuellement des relations et pratiques sociales à tous les niveaux. Nous nous intéressons à leurs implications politiques et à la façon dont les normes néolibérales peuvent changer à travers des pratiques de sensibilité.
https://ouci.dntb.gov.ua/en/works/4aLYeXg7/
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; care; discipline; europe; géographie; milieux universitaires; néolibéralisme; pratiques féministes; périodes historiques; recherche participative; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; thématiques; émotions

A voice from the South - Cooper, Anna Julia (University of North Carolina at Chapel Hill Library, 2017)
The first book by Anna J. Cooper, A Voice From the South, presents strong ideals supporting racial and gender equality as well as economic progress. It’s a forward-thinking narrative that highlights many disparities hindering the African American community. Anna J. Cooper was an accomplished educator who used her influence to encourage and elevate African Americans. With A Voice From the South, she delivers a poignant analysis of the country’s affairs as they relate to Black people, specifically Black women. She stresses the importance of education, which she sees as a great equalizer. Cooper considers it a necessary investment in not only the individual but the community. She also criticizes the depictions of African Americans in literature by some of the day’s most popular authors. She calls for more realistic portrayals that are both honest yet positive. Cooper provides an unflinching critique of mainstream America as it relates to the Black population. A Voice From the South broaches pivotal topics such as women’s rights, segregation and the need for higher education. With an eye-catching new cover, and professionally typeset manuscript, this edition of A Voice From the South is both modern and readable.
Première publication 1892 https://docsouth.unc.edu/church/cooper/cooper.html
Keywords: 1800-1899; afro-féminisme; amériques; approches et analyses; capitalisme; droits des femmes*; féminismes noirs; histoire et politique; militance; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; éducation; états-unis

Intersectional pedagogy : Complicating identity and social justice - Case, Kim A. (Routledge, 2017)
Intersectional Pedagogy explores best practices for effective teaching and learning about intersections of identity as informed by intersectional theory. Formatted in three easy-to-follow sections, this collection explores the pedagogy of intersectionality to address lived experiences that result from privileged and oppressed identities. After an initial overview of intersectional foundations and theory, the collection offers classroom strategies and approaches for teaching and learning about intersectionality and social justice. With contributions from scholars in education, psychology, sociology and women’s studies, Intersectional Pedagogy include a range of disciplinary perspectives and evidence-based pedagogy.
Keywords: approches et analyses; discipline; formations; féminisme décolonial; identités; intersectionnalité; justice sociale; outils; ouvrages de références; psychologie; pédagogie; ressource en ligne; sciences de l'éducation; sciences humaines; sociologie; thématiques; études de genres

Sex and gender considerations in transplant research: A scoping review - Laprise, Claudie; Cole, Katherine; Sridhar, Vikas Srinivasan; Marenah, Tida; Crimi, Cassandra; West, Lori; Foster, Bethany J.; Pilote, Louise; Sapir-Pichhadze, Ruth (Transplantation, 2017)
Background Despite the growing appreciation of the importance of sex and gender considerations in transplantation research, there is currently no framework or good practice guidelines for the appropriate handling of sex and gender issues in human allotransplantation research. Methods We will conduct a scoping review to synthesize the evidence on how matters of sex and gender have been handled in human allotransplantation research. We will survey the literature discussing sex and gender in relation to transplantation, including adult and pediatric patients, hematopoietic and solid organ transplant recipients as well as organ donors. We will search MEDLINE and Embase for literature discussing sex and gender in relation to transplantation. Two reviewers will independently evaluate the eligibility of all identified titles and abstracts for inclusion in the full text review, as well as data extraction. Descriptive data and information on how sex and gender have been considered in human transplantation research will be reported. Discussion This scoping review will be an important stepping stone towards the development of good practice guidelines on study design and analysis considerations when handling sex and gender issues in human transplantation research. This scoping review can also help identify methodological issues that restrict the translation of transplantation research findings into clinical practice related to underestimation of sex/gender differences. This review will ultimately identify major gaps, inform donor-recipient selection, guide personalized interventions, and prioritize research recommendations in human transplantation research. Electronic supplementary material The online version of this article (10.1186/s13643-017-0578-4) contains supplementary material, which is available to authorized users. Keywords: Sex, Gender, Transplantation, Scoping review
Keywords: 2000 à aujourd'hui; corps; discipline; médecine; projet charge mentale; périodes historiques; ressource en ligne; santé; sciences; thématiques; transplantation

A visual analysis of gender bias in contemporary anatomy textbooks - Parker, Rhiannon; Larkin, Theresa; Cockburn, Jon (Social Science & Medicine, 2017)
Les recherches empiriques ont établi un lien entre les préjugés sexistes dans l’enseignement médical et les attitudes et comportements négatifs des prestataires de soins de santé. Pourtant, cela fait plus de 20 ans que les recherches n’ont pas examiné dans quelle mesure les femmes et les hommes sont représentés de manière égale dans les manuels d’anatomie . En outre, les recherches antérieures n’ont pas exploré au-delà de la quantité de représentation pour examiner également les stéréotypes visuels de genre et, à la lumière des avancées théoriques dans le domaine de la recherche intersectionnelle, la relation entre les représentations du genre et les représentations de l’ethnicité, du type de corps, de la santé et de l’âge. Cette étude visait à déterminer l’existence et la représentation des préjugés sexistes dans les principaux manuels d’anatomie utilisés dans les écoles de médecine australiennes. Une analyse systématique du contenu visuel a été menée sur 6044 images dans lesquelles le sexe/genre pouvait être identifié, provenant de 17 principaux manuels d’anatomie publiés entre 2008 et 2013. Une analyse de contenu plus approfondie a été réalisée sur les 521 images narratives, qui représentent une histoire en cours, trouvées dans les mêmes manuels. Les résultats indiquent que la représentation du genre dans les images des manuels d’anatomie reste majoritairement masculine, sauf dans les sections spécifiques au sexe. En outre, d’autres formes de biais ont été constatées dans : la visualisation d’émotions, de rôles et de contextes stéréotypés en fonction du sexe ; le manque de diversité ethnique, d’âge et de type corporel ; et dans l’adhésion presque totale à une conception binaire sexe/genre. Malgré une attention accrue portée aux questions de genre en médecine, la représentation visuelle du genre dans les programmes médicaux continue d’être biaisée. La construction biaisée du genre dans les manuels d’anatomie conçus pour l’enseignement médical fournit aux futurs prestataires de soins de santé des informations inadéquates et irréalistes sur les patients.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; australie; corps; discous dominant; intersectionnalité; livres d'anatomie; océanie; projet charge mentale; périodes historiques; racisme; représentation des corps; régions géographiques; santé; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques

Radical reproductive justice: Foundation, theory, practice - Ross, Loretta; Roberts, Lynn; Derkas, Erika; Peoples, Whitney; Bridgewater Toure, Pamela (Feminist press, 2017)
Expanding the social justice discourse surrounding "reproductive rights" to include issues of environmental justice, incarceration, poverty, disability, and more, this crucial anthology explores the practical applications for activist thought migrating from the community into the academy. Radical Reproductive Justice assembles two decades’ of work initiated by SisterSong Women of Color Health Collective, creators of the human rights-based “reproductive justice” framework to move beyond polarized pro-choice/pro-life debates. Rooted in Black feminism and built on intersecting identities, this revolutionary framework asserts a woman's right to have children, to not have children, and to parent and provide for the children they have.
Keywords: afro-féminisme; approches et analyses; discipline; droit; droits des femmes*; intersectionnalité; justice reproductive; justice sociale; maternité; militance; santé; science politique et droit; sciences humaines; sociologie; thématiques

The vulva: Physiology and clinical management - Farage, Miranda A.; Maibach, Howard I. (CRC Press, 2017)
Compilation unique d'expertise sur l'anatomie, la physiologie, les questions cliniques et la recherche actuelle, ce manuel analyse la diversité des présentations en fonction de l'âge, de l'origine ethnique, des symptômes, des troubles, des diagnostics et de la toxicité. La deuxième édition de cette ressource essentielle pour toute personne prenant soin de patientes a été doublée pour inclure des chapitres supplémentaires. Tous les médecins, qu'ils soient dermatologues ou gynécologues, ainsi que ceux qui recherchent les preuves scientifiques et les symptômes, bénéficieront de l'expérience des contributeurs et éditeurs experts réunis ici.
Keywords: 2000 à aujourd'hui; corps; dermatologie; discipline; gynécologie; médecine; projet charge mentale; périodes historiques; santé; santé menstruelle; santé reproductive; santé sexuelle; sciences; sexualité; sexualité des femmes*; thématiques

Work–life balance of professional women in rural Spain - Baylina, Mireia; Garcia-Ramon, Maria Dolores; Porto, Ana Maria; Rodó-de-Zárate, Maria; Salamaña, Isabelle; Villarino, Montserrat (Gender, Place and Culture, 2017)
In some regions of Spain, well-educated women decide to move to the countryside to carry out their professional activities. This is a new phenomenon after many decades of female outmigration that also occurs in other European regions. Our aim is to explore how these professional women who decide to live in the countryside manage their work–life balance in this changing space. Our hypothesis is that these women, with high level of education and urban experience are more aware of gender inequality, have greater bargaining power, and therefore, achieve better work–life conciliation with their male partners. Research has been conducted through 60 in-depth interviews with women that have been analyzed through discourse analysis. The results show a complex situation. While these women are building the new ruralities with their work, skills, and insights, social norms concerning family responsibilities move more slowly. The research evidences aspects related to women’s well-being as well as brings the broad issue of care at the center of the feminist debate. © 2016 Informa UK Limited, trading as Taylor & Francis Group.
Number: 1
Keywords: 2000 à aujourd'hui; 2010-2019; care; conciliation famille-travail; division sexuelle du travail; espagne; europe; famille; milieu rural; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; thématiques; travail

Boundaried caring and gendered emotion management in hospice work - Cain, Cindy L. (Gender, Work and Organization, 2017)
Caring work, which is premised on caring for and caring about recipients, involves a great deal of emotion management. Feeling rules shape expectations about emotion management and are informally shared through workers’ narratives about quality work. Using qualitative data from hospice workers in the southwestern US, I find that narratives of quality within hospice include emotion-management skills such as listening, truly caring, keeping calm and maintaining boundaries. Through an analysis of how workers discuss and map skills onto individual women and men co-workers, this article highlights two gendered patterns. First, even when women and men are thought to share high-quality skills, the ways these skills are described reinforce naturalistic understandings of gender. Second, men are seen to hold a broad range of emotion-management skills, but women are not described as holding the most important emotion-management skill: keeping boundaries. Understanding this differential application of emotion-management skills helps us to understand how gender and gender inequality are reproduced within caring work. © 2017 John Wiley & Sons Ltd
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; intersectionnalité; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sexisme; soins palliatifs; systèmes d'oppressions; thématiques; travail; travail du care; travailleureuses de la santé; émotions; états-unis

Eating burnt toast: The lived experiences of female breadwinners in South Africa - Parry, Bianca Rochelle; Segalo, Puleng (Journal of International Women's Studies, 2017)
Dans la société sud-africaine, de nombreuses femmes ont surmonté les notions traditionnelles de genre en devenant les principaux soutiens de famille au foyer et en fournissant un soutien financier de base à leur famille. D'un point de vue phénoménologique, cet article met en contexte les expériences individuelles vécues par les femmes chefs de famille sud-africaines, en utilisant des données collectées auprès de dix femmes chefs de famille des provinces du Mpumalanga et du Gauteng respectivement à l'aide d'entretiens semi-structurés approfondis. En tenant compte de leurs expériences intersectionnelles en matière de genre, de race, ainsi que des pressions sociétales culturelles, traditionnelles et patriarcales, l'étude représente des voix qui ont longtemps été réduites au silence et marginalisées, afin de comprendre comment ces femmes donnent un sens à leur rôle de soutien de famille et négocient leur rôle de soutien de famille. Les résultats de cette étude mettent en lumière les divisions et les discriminations perpétuelles et archaïques liées au genre au sein de la société, qui continuent de se cacher derrière des constructions de réforme prônant l'égalité entre les sexes
Keywords: 2000 à aujourd'hui; afrique; afrique du sud; approches et analyses; famille; femmes cheffes de famille; intersectionnalité; patriarcat; projet charge mentale; périodes historiques; régions géographiques; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; travail

The new work regime in Nunavut: A gender perspective - Quintal-Marineau, Magalie (The Canadian Geographer / Le Géographe canadien, 2017)
Cet article examine le paysage économique du Nunavut à partir de l'activité économique des femmes inuites. Dans le Nunavut contemporain, l'identité de genre joue un rôle déterminant dans les dynamiques de travail salarié, particulièrement au sein des familles. Bien que les femmes inuites occupent une place centrale sur le marché du travail, dans les activités familiales et domestiques, et que leur participation au développement du nord n'ait cessé de croître, jusqu'à ce jour peu d'études se sont intéressées aux dynamiques de genre dans ce contexte. Afin d'examiner l'organisation du travail salarié à trois échelles — la communauté, la famille et l'individu — l'article s'appuie sur les récits individuels de 29 familles recueillis par l'auteur dans la communauté de Kangiqtugaapik, Nunavut entre 2011 et 2013.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; environnement; femmes* inuites; histoire et politique; maternité; nunavut; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; thématiques; travail; travail salarié

The lived experiences of black undergraduate lesbian students at a rural South African university - Nela, K.; Vawdab, N.; Mbokodoc, L.; Govender, S. (Gender and Behaviour, 2017)
Malgré l'acceptation croissante des personnes lesbiennes, gays, bisexuelles, transgenres et intersexes (LGBTI), de nombreuses études indiquent encore que de nombreuses discriminations existent toujours. Les lesbiennes d'Afrique australe sont quotidiennement victimes de violences physiques et verbales et de viols correctifs. Le but de cette étude était d'explorer les expériences vécues par des étudiantes lesbiennes noires de premier cycle dans une université rurale en Afrique du Sud. Une approche de recherche qualitative utilisant un plan de recherche phénoménologique a été utilisée. L'échantillon était composé de quinze étudiantes lesbiennes noires de premier cycle âgées de 18 à 25 ans. Les données ont été collectées dans deux groupes de discussion et analysées à l'aide d'une analyse phénoménologique interprétative (IPA). L'homophobie, le harcèlement, y compris les agressions physiques, et la non-acceptation étaient des expériences quotidiennes chez les participantes lesbiennes. Cela incluait la discrimination de la part des pairs, du personnel universitaire et des organisations religieuses. Des expériences positives, comme la rencontre de nouveaux amis partageant la même orientation sexuelle et la découverte de l'université comme espace libre pour explorer leur sexualité, ont été trouvées.
Number: 3
Keywords: afrique; afrique du sud; approches et analyses; discipline; droits des femmes*; hétérosexisme; lesbophobie; personnes lesbiennes; psychologie; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; étudiantes de premier cycle

Gender (in)securities: Surveillance and transgender bodies in post 9/11 era of neoliberalism - Quinan, Christine (Security/mobility: politics of movement, 2017)
https://www.jstor.org/stable/j.ctt1wn0s9r.14
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; citoyenneté; corps; genre; hétérosexisme; identités; législation; personnes trans*; périodes historiques; queer; racisme; ressource en ligne; solidarité; systèmes d'oppressions; thématiques; violences

Men's intrusion, women's embodiment: a critical analysis of street harassment - Vera-Gray, Fiona (Routledge, 2017)
Research on violence against women tends to focus on topics such as sexual assault and intimate partner violence, arguably to the detriment of investigating men’s violence and intrusion in women’s everyday lives. The reality and possibility of the routine intrusions women experience from men in public space – from unwanted comments, to flashing, following and frottage – are frequently unaddressed in research, as well as in theoretical and policy-based responses to violence against women. Often at their height during women’s adolescence, such practices are commonly dismissed as trivial, relatively harmless expressions of free speech too subjective to be legislated against. Based on original empirical research, this book is the first of its kind to conduct a feminist phenomenological analysis of the experience for women of men’s stranger intrusions in public spaces. It suggests that intrusion from unknown men is a fundamental factor in how women understand and enact their embodied selfhood. This book is essential reading for academics and students involved in the study of violence against women, feminist philosophy, applied sociology, feminist criminology and gender studies.
Keywords: 2000 à aujourd'hui; 2010-2019; agentivité; angleterre; approches et analyses; corps; discipline; europe; harcèlement de rue; patriarcat; phénoménologie; périodes historiques; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; violences

Justice is indivisible: Palestine as a feminist issue - Elia, Nada (Decolonization: Indigeneity, Education & Society, 2017)
⠀⠀⠀⠀⠀⠀⠀⠀⠀
Number: 1
Keywords: approches et analyses; asie; cours; féminisme arabe; féminisme décolonial; histoire et politique; palestine; pol4212; premier cycle; ressource en ligne; régions géographiques; sofia; système colonial; systèmes d'oppressions; thématiques

Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

The mask .. Maya Angelou delivers it with the powerful tragedy and dignity that miss Rosie inspired. - Angelou, Maya (2017)
The mask .. Maya Angelou delivers it with the powerful tragedy and dignity that miss Rosie inspired..
Keywords: afro-féminisme; amériques; approches et analyses; cours; fem3100; féminisme afroaméricain; militance; poésie; premier cycle; ressource en ligne; régions géographiques; thématiques; états-unis

Gender: Psychological perspectives - Brannon, Linda (Routledge, 2017)
"Gender: Psychological Perspectives" synthesizes the latest research on gender to help students think critically about the differences between research findings and stereotypes, provoking them to examine and revise their own preconceptions. The text examines the behavioral, biological, and social contexts in which women and men express gendered behaviors. The text's unique pedagogical program helps students understand the portrayal of gender in the media and the application of gender research in the real world. – From publisher's description. Contenu : Preface – Acknowledgements – About the author – The study of gender – Researching sex and gender – Gender stereotypes: masculinity and femininity – Hormones and chromosomes – Theories of gender development – Developing gender identity – Intelligence and cognitive abilities – Emotion – Relationships – Sexuality – School – Careers and work – Health and fitness – Stress, coping, and psychopathology – Treatment for mental disorders – How different? – References – Index.
Section: xix, 539 pages ; 26 cm
Keywords: approches et analyses; biologie; comportements sexuels; cours; différence des sexes; discipline; discours dominant; identité sexuelle; maternité; paternité; premier cycle; psy4910; psychologie; relations amoureuses; santé; santé mentale; sciences; sciences humaines; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; violences; violences sexuelles; études de genres

Creating ourselves: works from the ISelf Collection : the self in art - Butler, Emily; Stobbs, Candy; Whitechapel Art Gallery. (Whitechapel Gallery, 2017)
"From Surrealist selfies to feminist self-portraiture, the ISelf Collection explores identity and the human condition through the central themes of birth, death, sexuality, love, pain and joy. Taking the display of the collection at Whitechapel Gallery as its springboard, this book looks generally at the question of the self in modern and contemporary art, and the ways in which artists are thinking about being and identity as an individual, in relation to others, to society and the wider world. Featuring works by a world-class roster of artists including Francis Alys, Fiona Banner, Lynda Benglis, Louise Bourgeois, Tracey Emin, Alex Katz, Sarah Lucas, Mike Nelson, Cindy Sherman, John Stezaker and Wolfgang Tillmans, this fully illustrated catalogue also includes essays by Glenn Adamson, Frances Borzello, Nicholas Cullinan and Amelia Jones, as well as a selection of quotes by influential writers and theorists as chosen by some of the artists included."
Keywords: arts; arts visuels et médiatiques; corps; cours; discipline; har4600; identités; premier cycle; thématiques

You play the girl: on Playboy bunnies, Stepford wives, train wrecks, and other mixed messages - Chocano, Carina (Houghton Mifflin Harcourt, 2017)
"Who is "the girl"? Look to movies, TV shows, magazines, and ads and the message is both clear and not: she is a sexed-up sidekick, a princess waiting to be saved, a morally infallible angel with no opinions of her own. She's whatever the hero needs her to be in order to become himself. She's an abstraction, an ideal, a standard, a mercurial phantom. In You Play the Girl, Chocano blends formative personal stories with insightful and emotionally powerful analysis. Moving from Bugs Bunny to Playboy Bunnies, Flashdance to Frozen, the progressive '70s through the backlash '80s, the glib '90s, and the pornified aughts–and at stops in between–she explains how growing up in the shadow of "the girl" taught her to think about herself and the world and what it means to raise a daughter in the face of these contorted reflections. In the tradition of Roxane Gay, Rebecca Solnit, and Susan Sontag, Chocano brilliantly shows that our identities are more fluid than we think, and certainly more complex than anything we see on any kind of screen."–Page 4 of cover.
Section: xxvi, 275 pages : illustration ; 21 cm
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; com5170; communication; cours; discipline; discours dominant; féminisme pop; histoire et politique; journalisme; premier cycle; périodes historiques; représentation des femme*; sofia; systèmes d'oppressions; thématiques

Desire change: contemporary feminist art in Canada - Davis, Heather M. (Heather Margaret); Mentoring Artists for Women's Art (McGill-Queen's University Press, 2017)
"In the resistance to the violence of gender-based oppression, vibrant - but often ignored - worlds have emerged, full of nuance, humour, and beauty. Correcting a glaring omission of writing about contemporary feminist work by Canadian artists, Desire Change considers the resurgence of feminist art, thought, and practice in the past decade by examining artworks that respond to themes of diversity and desire. Essays by historians, artists, and curators present an overview of a range of artistic practices including performance, installation, video, textiles, and photography. Contributors address the desire for change through three central frames: how feminist art has significantly contributed to the complex understanding of gender as it intersects with sexuality and race; the necessary critique of patriarchy and institutions as they relate to colonization within the Canadian national-state; and the ways in which contemporary critiques are formed and expressed. The resulting collection addresses art through an activist lens to examine intersectional feminism, decolonization, and feminist institution building in a Canadian context. Heavily illustrated with representative works, Desire Change raises both the stakes and the concerns of contemporary feminist art, with an understanding that feminism is always and necessarily plural."– Provided by publisher.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; canada; cours; discipline; femmes* artistes; féminisme décolonial; har4600; histoire de l'art; histoire et politique; intersectionnalité; patriarcat; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Girlhood interrupted: The erasure of Black girls' childhood - Epstein, Rebecca; Blake, Jamilia J.; González, Thalia (Georgetown Law, Center on Poverty and Inequality, 2017)
This groundbreaking study by the Georgetown Law Center on Poverty and Inequality provides—for the first time— data showing that adults view Black girls as less innocent and more adult-like than their white peers, especially in the age range of 5–14. The report builds on similar results that have emerged from studies of adult perceptions of Black boys. In 2014, for example, research by Professor Phillip Goff and colleagues revealed that beginning at the age of 10, Black boys are more likely than their white peers to be misperceived as older, viewed as guilty of suspected crimes, and face police violence if accused of a crime.1 SNAPSHOT OF THE DATA Compared to white girls of the same age, survey participants perceive that • Black girls need less nurturing • Black girls need less protection • Black girls need to be supported less • Black girls need to be comforted less • Black girls are more independent • Black girls know more about adult topics • Black girls know more about sex These results are profound, with far-reaching implications. Our findings reveal a potential contributing factor to the disproportionate rates of punitive treatment in the education and juvenile justice systems for Black girls.
http://arks.princeton.edu/ark:/88435/dsp01tx31qm28z
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; cours; discipline; droit; fem3300; filles noires; genre; identités LGBTQIA2+; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique et droit; sexisme; systèmes d'oppressions; thématiques; états-unis

THE COLOURED WOMEN’S CLUB OF MONTREAL, 1902-1940: African-Canadian women confronting anti-black racism - Este, David; Sato, Christa; McKenna, Darcy (Canadian Social Work Review, 2017)
À ce jour, il existe très peu d’écrits sur la contribution des personnes d’ascendance africaine à l’histoire de l’assistance sociale canadienne. À partir de sources secondaires et archivistiques, nous analysons la contribution du Club des femmes de couleur de Montréal (CFCM) au bien-être de la communauté noire de Montréal entre 1902 et 1940 du point de vue du racisme contre les Noir.e.s et du féminisme afro-canadien. Le CFCM a joué un rôle prépondérant dans ce bien-être en étant l’un des grands soutiens auprès des membres aux prises avec d’importantes difficultés dans une société où le racisme était omniprésent et où les perspectives d’avenir pour les hommes et les femmes étaient fortement limitées. Le club a organisé plusieurs activités qui ont permis aux membres de la communauté de survivre dans un milieu hostile aux personnes d’ascendance africaine. Il a ainsi été d’un grand secours et a favorisé un sentiment de communauté chez les Noir.e.s de Montréal. Nous avançons que, grâce aux efforts de ce club durant cette période, les Afro-Canadiennes sont d’abord devenues des actrices clés de la communauté et ensuite les premières intervenantes sociales. Il est impératif que les travailleurs sociaux reconnaissent la contribution des femmes engagées dans le CFCM afin de faire contrepoids aux récits historiques de notre profession qui proviennent surtout d’une culture hégémonique blanche.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; amériques; approches et analyses; canada; cours; fem3100; femmes* afro-descendantes; histoire et politique; militance; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques

In the name of women's rights: the rise of femonationalism - Farris, Sara R. (Duke University Press, 2017)
Sara R. Farris examines the demands for women's rights from an unlikely collection of right-wing nationalist political parties, neoliberals, and some feminist theorists and policy makers. Focusing on contemporary France, Italy, and the Netherlands, Farris labels this exploitation and co-optation of feminist themes by anti-Islam and xenophobic campaigns as “femonationalism.” She shows that by characterizing Muslim males as dangerous to western societies and as oppressors of women, and by emphasizing the need to rescue Muslim and migrant women, these groups use gender equality to justify their racist rhetoric and policies. This practice also serves an economic function. Farris analyzes how neoliberal civic integration policies and feminist groups funnel Muslim and non-western migrant women into the segregating domestic and caregiving industries, all the while claiming to promote their emancipation. In the Name of Women's Rights documents the links between racism, feminism, and the ways in which non-western women are instrumentalized for a variety of political and economic purposes.
Disponible en ligne: https://www-jstor-org.proxy.bibliotheques.uqam.ca/stable/j.ctv11sn2fp Donné à lire au cours POL4212, "Introduction", p1-17.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; approches et analyses; cours; discipline; europe; france; féminisme islamique; fémonationalisme; histoire et politique; intersectionnalité; italie; justice sociale; pays-bas; pol4212; premier cycle; périodes historiques; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; systèmes d'oppressions; thématiques

The Routledge companion to feminist philosophy - Garry, Ann; Khader, Serene J.; Stone, Alison (Routledge, 2017)
"The Routledge Companion to Feminist Philosophy is an outstanding guide and reference source to the key topics, subjects, thinkers, and debates in feminist philosophy. Fifty-six chapters, written by an international team of contributors specifically for the Companion, are organized into five sections: (1) Engaging the Past; (2) Mind, Body, and World; (3) Knowledge, Language, and Science; (4) Intersections; (5) Ethics, Politics, and Aesthetics. The volume provides a mutually enriching representation of the several philosophical traditions that contribute to feminist philosophy. It also foregrounds issues of global concern and scope; shows how feminist theory meshes with rich theoretical approaches that start from transgender identities, race and ethnicity, sexuality, disabilities, and other axes of identity and oppression; and highlights the interdisciplinarity of feminist philosophy and the ways that it both critiques and contributes to the whole range of subfields within philosophy."–The publisher.
Le chapitre 22 de Miranda Fricker et Katharine Jenkins, “Epistemic injustice, ignorance, and trans experiences” a été donné en lecture au cours FEM9000.
Keywords: afro-féminisme; approches et analyses; autonomie; bioéthique; care; cours; cycles supérieurs; discipline; environnement; esthétique; fem9000; féminisme africain; féminisme autochtone; féminisme décolonial; féminismes noirs; identité; injustices épistémiques; intersectionnalité; justice sociale; matérialité; objectivité; outils; ouvrages de références; philosophie; philosophie féministe; phénoménologie; politique de genre; queer; rationnalité; religion; sciences humaines; subjectivité; thématiques; théorie du contrat social; transféminisme; écologie; éthique; éthique du care; études critiques de la race; études critiques du handicap

Making space for Indigenous feminism - Green, Joyce A. (Fernwood Publishing, 2017)
The 2007 first edition of this book proposed that Indigenous feminism was a valid and indeed essential theoretical and activist position, and introduced a roster of important Indigenous feminist contributors. The book has been well received nationally and internationally. It has been deployed in Indigenous Studies, Law, Political Science, and Women and Gender Studies in universities and appears on a number of doctoral comprehensive exam reading lists. The second edition, Making More Space, builds on the success of its predecessor, but is not merely a reiteration of it. Some chapters from the first edition are largely revised. A majority of the chapters are new, written for the second edition by important new scholars and activists. The second edition is more confident and less diffident about making the case for Indigenous feminism and in deploying a feminist analysis. The chapters cover issues that are relevant to some of the most important issues facing Indigenous people–violence against women, recovery of Indigenous self-determination, racism, misogyny, and decolonisation. Specifically, new chapters deal with Indigenous resurgence, feminism amongst the Sami and in Aboriginal Australia, neoliberal restructuring in Oaxaca, Canada's settler racism and sexism, and missing and murdered Indigenous women in Canada."– Résumé de l'éditeur.
Le texte de Eberts, Mary (2017). Being an Indigenous Women is a “High Risk Lifestyle” a été donné en lecture au cours POL4105.
Keywords: amériques; approches et analyses; australie; canada; cours; discipline; droits des femmes*; droits des personnes autochtones; féminisme autochtone; histoire et politique; justice sociale; mexique; militance; océanie; patriarcat; pol4105; premier cycle; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones; études décoloniales; études féministes

Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

The Routledge handbook of epistemic injustice - Kidd, Ian James; Medina, José; Pohlhaus, Gaile M. (Routledge, 2017)
In the era of information and communication, issues of misinformation and miscommunication are more pressing than ever. Epistemic injustice–one of the most important and ground-breaking subjects to have emerged in philosophy in recent years–refers to those forms of unfair treatment that relate to issues of knowledge, understanding, and participation in communicative practices. The Routledge Handbook of Epistemic Injustice is an outstanding reference source to the key topics, problems, and debates in this exciting subject. The first collection of its kind, it comprises over thirty chapters by a team of international contributors, divided into five parts: Core Concepts; Liberatory Epistemologies and Axes of Oppression; Schools of Thought and Subfields within Epistemology; Socio-political, Ethical, and Psychological Dimensions of Knowing; Case Studies of Epistemic Injustice. As well as fundamental topics such as testimonial and hermeneutic injustice and epistemic trust the Handbook includes chapters on important issues such as social and virtue epistemology, objectivity and objectification, implicit bias, and gender and race. Also included are chapters on areas in applied ethics and philosophy, such as law, education, and healthcare. The Routledge Handbook of Epistemic Injustice is essential reading for students and researchers in ethics, epistemology, political philosophy, feminist theory, and philosophy of race. It will also be very useful for those in related fields, such as cultural studies, sociology, education, and law.
Le chap 10 de Patricia Hill Collins, “Intersectionality and Epistemic Injustice” a été donné en lcture au cours FEM9000. Le chap 14 de Kim Hall, “Queer Epistemology and Epistemic Injustice” a été donné en lecture au cours FEM9000. Le chap 15 de Rachel McKinnon, “Allies behaving badly: Gaslighting as epistemic injustice” a été donné en lecture au cours FEM9000. Le chap 16 de Shelley Tremain, “Knowing Disability Differently” a été donné au cours FEM9000. Le chap 33 de Anastasia Scrutton, “Epistemic Injustice and Mental Illness” a été donné en lecture au cours FEM9000. Le chap 34 de Rebecca Tsosie, “Indigenous peoples, anthropology, and the legacy of epistemic injustice” a été donné au cours FEM9000.
Keywords: approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; injustices épistémiques; intersectionnalité; outils; ouvrages de références; philosophie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; épistémologie; éthique; études critiques de la race; études critiques du handicap

Deer Woman: an anthology - LaPensée, Elizabeth; Alvitre, Weshoyot; Stonefish, Patty; Vasquez, Allie; Naragon, Rebecca; Thunder, Jonathan; Native Realities (Firm); Arming Sisters (Organization) (Native Realities, LLC, 2017)
Based on the true stories of Indigenous women throughout the world, Deer Woman: An Anthology is an extension of the Deer Woman: A Vignette, comic book that itself is a powerful expression and weaves the stories of Deer Woman into a modern narrative of the struggles of Indigenous women in North America. This anthology features the work of more than a dozen Native women sharing stories of survival, empowerment, and healing. Edited by Elizabeth LaPensée and Weshoyot Alvitre and featuring the work of: Patty Stonefish, Allie Vasquez, Mia Casesa, Darcie Little Badger, Tara Ogaick, Kimberly Robertson, Barbara Kenmille, Maria Wolf Lopez, Tatum Bowie, Jackie Fawn, Rebecca Roanhorse, Carolyn Dunn, Nashoba Dunn-Anderson, and more, this anthology is an important addition to the current conversation about violence against women, especially Native women.-from publisher's website.
Section: 1 volume (unpaged) : chiefly illustrations (some color) ; 26 cm
Keywords: amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; bande-dessinée; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

Black history month: Diversity and the British female suffrage movement - Mukherje, Sumita (The Fawcett Society, 2017)
The fight for the female vote was not solely a British, or a ‘white’ concern, writes historian Sumita Mukherjee.
https://www.fawcettsociety.org.uk/blog/diversity-british-female-suffrage-movement
Keywords: approches et analyses; asie; cours; droits des femmes*; europe; fem1000; féminisme décolonial; inde; mouvements des femmes*; premier cycle; royaume-uni; régions géographiques; suffragettes; thématiques

Negotiating Parental designations among trans parents' families: An ecological model of Parental identity - Petit M.-P.; Julien D.; Chamberland L. (Psychology of Sexual Orientation and Gender Diversity, 2017)
Parental designations contribute to construct parental identity in the eyes of the child, the parent, and the generalized others. In a hetero/cisnormative context that offers only 2 options for parental identity (male fathers and female mothers), this study (a) provided an overview of the parental designations of trans people and their evolution as parents transitioned, (b) and generated a model of factors associated with the choice of posttransition parental designations. Semistructured interviews guided by the Bronfenbrenner’s ecological model (1988) were administered to 24 Canadian trans parents. The content of the interviews was analyzed using thematic analyses. Results showed that the choice of parental designations was influenced by the timing of childbirth, parents’ consideration of normative strains, negotiation with their children, and issues related to public spaces. Overall, trans parental identity appeared as a multidimensional, multidetermined, nonbinary, and fluid identity in a context of nonalignment between the sex assigned at birth and gender identity. Institutional forms and legislation relative to parenting and birthing must acknowledge the diversity of parental identity and designations.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; famille; identités LGBTQIA2+; maternité; parentalité; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; soc2264; sociologie; thématiques; transféminisme

Terrorist assemblages: Homonationalism in queer times - Puar, Jasbir K. (Duke University Press, 2017)
Dans ce travail révolutionnaire, Jasbir K. Puar soutient que les configurations de la sexualité, de la race, du genre, de la nation, de la classe et de l'ethnicité se réalignent par rapport aux forces contemporaines de la sécurisation, du contre-terrorisme et du nationalisme. Elle examine comment la politique libérale intègre certains sujets queer dans le giron de l'État-nation, à travers des développements tels que la reconnaissance juridique inhérente à l'annulation des lois anti-sodomie et la prolifération d'une représentation plus dominante. Ces incorporations ont fait passer de nombreux queers de leur construction en tant que figures de la mort (via l'épidémie de sida) à des sujets liés aux idées de vie et de productivité (mariage gay et parenté reproductive). Puar soutient cependant que cette inclusion ténue de certains sujets queer dépend de la production de populations de corps terroristes orientalisés. Les idéologies hétéronormatives sur lesquelles l'État-nation américain s'est longtemps appuyé sont désormais accompagnées d'idéologies homonormatives qui reproduisent des idéaux raciaux, de classe, de genre et nationaux étroits. Ces « homonationalismes » sont déployés pour distinguer les patriotes américains « proprement hétéros » et maintenant « proprement homos » des sosies terroristes sexualisés et racialisés de manière perverse – en particulier les sikhs, les musulmans et les arabes – qui sont bouclés pour détention et détention. déportation. Puar combine la théorie féministe et queer transnationale, la biopolitique foucaldienne, la philosophie deleuzienne et la critique des technosciences, et puise dans un éventail extraordinaire de sources, notamment des textes gouvernementaux, des décisions juridiques, des films, la télévision, des données ethnographiques, des médias queer et des documents et manifestes d'organisation militante. . En s'intéressant à divers événements et phénomènes culturels, elle met en évidence des liens gênants entre terrorisme et sexualité : dans les réponses féministes et queer aux photographies d'Abu Ghraib, dans les réponses triomphales à l'arrêt Lawrence de la Cour suprême abrogeant les lois anti-sodomie, dans les mesures prises par les Américains sikhs et Queers de la diaspora sud-asiatique prennent pour éviter d'être profilés comme des terroristes, et ce que Puar soutient est une islamophobie croissante au sein de l'organisation mondiale queer
https://search.ebscohost.com/login.aspx?direct=true&scope=site&db=nlebk&db=nlabk&AN=1691715
Keywords: approches et analyses; cours; discipline; discours dominant; fem3400; homonationalisme; identités LGBTQIA2+; pol4212; premier cycle; queer; racisme; ressource en ligne; science politique et droit; sexualité; système colonial; systèmes d'oppressions; thématiques; violences; études de genres; études décoloniales

As we have always done: Indigenous freedom through radical resistance - Simpson, Leanne Betasamosake (University of Minnesota Press, 2017)
Across North America, Indigenous acts of resistance have in recent years opposed the removal of federal protections for forests and waterways in Indigenous lands, halted the expansion of tar sands extraction and the pipeline construction at Standing Rock, and demanded justice for murdered and missing Indigenous women. In As We Have Always Done, Leanne Betasamosake Simpson locates Indigenous political resurgence as a practice rooted in uniquely Indigenous theorizing, writing, organizing, and thinking. Indigenous resistance is a radical rejection of contemporary colonialism focused around the refusal of the dispossession of both Indigenous bodies and land. Simpson makes clear that its goal can no longer be cultural resurgence as a mechanism for inclusion in a multicultural mosaic. Instead, she calls for unapologetic, place-based Indigenous alternatives to the destructive logics of the settler colonial state, including heteropatriarchy, white supremacy, and capitalist exploitation.
Keywords: amérique du nord; amériques; approches et analyses; autochtones; colonialisme; com5170; cours; discours dominant; fem1300; histoire et politique; militance; pol4212; premier cycle; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences

Bodies as resistance: Claiming the political act of being oneself (2017)
The power of accepting ourselves begins by accepting our bodies. Poet, Activist, Author Sonya Renee Taylor is an author, poet, spoken word artist, speaker, humanitarian and social justice activist, educator, and founder of The Body is Not An Apology movement, an international movement and organization committed to radical self-love and body empowerment as the foundational tool for social justice and global transformation. Sonya’s work as an award winning Performance Poet, activist and transformational leader continues to have global reach. Sonya is a former national and international poetry slam champion, author, educator and activist who has mesmerized audiences across the US, New Zealand, Australia, Germany, England, Scotland, Sweden, Canada and the Netherlands as well as in prisons, mental health treatment facilities, homeless shelters, universities, festivals and public schools across the globe. http://www.sonya-renee.com
Producers: _:n22012
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; corps; cours; fem3300; militance; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques; états-unis

Credibility Excess and the Social Imaginary in Cases of Sexual Assault - Yap, Audrey S (Feminist Philosophy Quarterly, 2017)
This paper will connect literature on epistemic injustice with literature on victims and perpetrators, to argue that in addition to considering the credibility deficit suffered by many victims, we should also consider the credibility excess accorded to many perpetrators. Epistemic injustice, as discussed by Miranda Fricker, considers ways in which someone might be wronged in their capacity as a knower. Testimonial injustice occurs when there is a credibility deficit as a result of identity-prejudicial stereotypes. However, criticisms of Fricker have pointed out that credibility is part of a more complex system that includes both deficits and excesses. I will use these points to argue that we should look closer at sources of credibility excess in cases of sexual assault. This means that in addition to considering sources of victim blaming by looking at ways in which “ideal” victims are constructed, we also need to consider ways in which “ideal” perpetrators are constructed.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; injustices testimoniales; injustices épistémiques; inégalités; philosophie; philosophie féministe; privilèges; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; éxcès de crédibilité